16S rRNA gene sequence analysis of a Brucella melitensis infection misidentified as Bergeyella zoohelcum - Dash, Nihar; Panigrahi, Debadatta; Al-Zarouni, Mansour; Mishra, Sanjeet (The Journal of Infection in Developing Countries, 2011)
Misidentification of Brucella species from clinical specimens using commercial bacterial identification systems is a recurring problem. An isolate from a bacterimic patient was identified as Bergeyella zoohelcum by MicroScan Walk-Away (Siemens Healthcare Diagnostics Inc., West Sacramento, CA, USA) and as Brucella melitensis by Vitek 2 system (bioMérieux Inc., Durham, NC, USA). Because of this identification ambiguity by the two automated bacterial identification systems we performed 16S rRNA sequencing and serotyping of the isolate and confirmed it as a Brucella spp. Combining the sequence data with the Vitek 2 system data we conclude that the infection was caused by B. melitensis.